Article RETRACTED due to manipulation by the authors Effects of Physical Activity on Physical Health, Behavior and Personality by Social Status of Urban and Rural Children: A Systematic Review - Ahmad Chaeroni; Nuridin Widya Pranoto; Kamal Talib; Mottakin Ahmed; Mohammad Khishe; Ardo Okilanda; Mohd Nizam Lani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study investigates the impact of physical activity on children's physical health, behavior and personality by considering differences in social status in urban and rural environments. Using mixed methods, we combined surveys, observations and psychological measurements to gain in-depth insights. Involving children of different age groups (12-16 years old) from both neighborhoods (urban and rural), this study looked at the level, frequency, and type of physical activity they engaged in. In evaluating physical health, not only physical aspects such as fitness and body mass index were considered, but also factors such as sleep patterns and eating habits. In addition, the children's behavior and personality were also analyzed using tested measurement tools. This study aims to uncover significant differences and patterns that may emerge between urban and rural children in response to physical activity. The findings from this study are expected to provide an in-depth picture of the complex relationship between physical activity, social status and children's well-being. The practical implication of this study is to develop more focused interventions to promote physical activity in both settings, taking into account their social context. This study is a Systematic Literature Review (SLR) that has been published in the Web of Science, Transport Research International Documentation (TRID), Scopus, Medline, and Google Scolar. Data were analyzed using the process of selecting articles used utilizing the PRISMA. By presenting these findings comprehensively, this study contributes to a better understanding of child health efforts in different urban and rural environments. Physical activity interventions were effective in changing behavior and improving personality traits of children in both urban and rural areas. The importance of adaptation of intervention strategies depending on the environmental context recommends further research: Include more variables, consider psychological aspects in more depth, and explore the role of social factors in intervention success.